Language Policies and Teacher Strategies for Promoting Psychological Inclusiveness in the Diverse Classroom in Aba Education Zone - Francisca Ifeoma Ehiemere; Emmanuel Lucas Nwachukwu; Osuji Columbus Otuosorochi; Regina Ijeoma Ukwuoma (Darul Yasin Al Sys, 2026)
This study examined the influence of language policies on classroom inclusivity and the strategies used by teachers to promote psychological inclusiveness in linguistically diverse secondary school classrooms in Aba Education Zone, Abia State, Nigeria. A descriptive survey design was adopted, involving 200 junior and senior secondary school teachers selected through stratified random sampling. Data were collected using a structured four-point Likert-scale questionnaire and analyzed through descriptive statistics and inferential statistics, including independent samples t-test and one-way ANOVA at α = 0.05. The findings indicate that language policies exerted limited practical influence on psychological inclusiveness, as reflected in a cluster mean of 2.48, revealing a persistent gap between policy intent and classroom implementation. Despite this limitation, teachers employed various inclusive strategies, including differentiated instruction, code-switching, and culturally responsive pedagogy, with a cluster mean of 2.79. The major barriers to implementation included inadequate training, resource deficits, and weak administrative support, with a cluster mean of 2.67. No statistically significant differences were found in teachers’ use of inclusive strategies based on gender, t = 0.743, p = .458, or teaching experience, F = 1.032, p = .380. The study concludes that although language policies provide a formal basis for inclusive education, their practical impact remains constrained by institutional and pedagogical barriers. This study contributes empirical evidence on the disconnect between language policy and classroom practice in a linguistically complex Nigerian urban context and offers implications for policymakers, curriculum designers, and teacher educators in strengthening teacher preparation, resource provision, and administrative support for psychologically inclusive classrooms.